Facility layout design of bag and apparel factory with systematic layout planning and computerized relative allocation of facilities technique method - Fitrian, Alvin Noor; Lestari, Dwi (OPSI, 2024)
The high market attractiveness index and competitive position made Dewi Media Lestari invest in building a new factory. The factory specifically is used to produce convection products and apparel. Development is carried out using a systematic layout planning and computerized relative allocation of facilities technique. The objective of this research is to obtain an ideal layout that can minimize the distance between departments. As a result, there are nine departments with a total area of 385 m2 consisting of 18 m2loading dock department, 36 m2 raw material department, 86 m2cutting department, 42 m2 branding department, 21 m2 screen printing department, 105 m2 sewing department, 28 m2 finishing department, 28 m2 packing department, and 21 m2 warehouse department. Material handling costs for the initial layout produced using the systematic layout planning method are IDR 29,808.95 per day. After adjusting with Computerized Relative Facility Allocation Technique, the most ideal final layout was produced with minimal material handling costs of IDR 24,411.40 per day.